Digital technologies in the manufacture of packaging products - Savchenko, O. M. (ТОВ «Видавництво Ліра-К», 2025)
An overview of the main digital technologies (AR, VR, AI, and digital printing methods) used in the design, development, and manufacturing of packaging products throughout their life cycle is provided.
Keywords: virtual reality; augmented reality